2022
DOI: 10.46384/jmsf.1169162
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Different Feeds on Brine Shrimp, Artemia parthenogenetica Culture

Abstract: In this study, Artemia parthenogenetica was fed with either Spirulina (S), yeast (Y), rice bran (R), oat (O) or their combinations in 10 experimental groups in triplicate for 20 days in laboratory conditions and growth, biomass, feed conversion rate (FCR), specific growth rate (SGR), survival rate, crude protein, crude lipid contents were determined. The highest average body length obtained at the end of the experiment was 2.805±0.003 mm in treatments (S) and (SYR), and the highest average individual dry weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Artemia fed spirulina powder showed better length growth compared to feed containing soybeans. Some research also showed that feeding spirulina powder provided the best growth performance compared to other comparison diets [25,27,28] . Arumugam et al [27] obtained length growth of Artemia fed with spirulina powder of 1.1±0.6 cm at 20 days of rearing, and Khadka et al [28] obtained 8.7 mm at 21 days of rearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artemia fed spirulina powder showed better length growth compared to feed containing soybeans. Some research also showed that feeding spirulina powder provided the best growth performance compared to other comparison diets [25,27,28] . Arumugam et al [27] obtained length growth of Artemia fed with spirulina powder of 1.1±0.6 cm at 20 days of rearing, and Khadka et al [28] obtained 8.7 mm at 21 days of rearing.…”
Section: Discussionmentioning
confidence: 99%
“…Spirulina is rich in phytonutrients that exhibit potent antioxidant properties and contains high number of natural pigments as bioactive component [23] . According to Saharan & Jood [24] , spirulina powder contains 71.90% protein, 1.27% lipid, and 13.63% carbohydrates, whereas Qaranjiki and Kırkağaç [25] found that nutrition content of spirulina powder including protein, lipid, and carbohydrate were 60.94%, 4.57%, and 28.07% respectively. Spirulina powder was also used as feed ingredients in several Artemia rearing studies [26,27,28] .…”
Section: Introductionmentioning
confidence: 99%